Efektivitas Kerja Tim Evaluator dalam Penilaian Sistem Akuntabilitas Kinerja Instansi Pemerintah (SAKIP) di Lingkungan Pemerintah Kabupaten Solok (Studi pada Inspektorat Daerah Kabupaten Solok) - Dinda Mutiarani Jamil; Sinta Westika Putri (Lembaga Yasin AlSys, 2026)
The implementation of the Government Agency Performance Accountability System (SAKIP) is an important instrument in realizing transparent, accountable, and results-oriented governance. In its evaluation process, the work effectiveness of the Evaluation Team is an important factor that determines the quality of assessment and the accuracy of recommendations for improving the performance of regional apparatus organizations. This study aims to analyze the work effectiveness of the Evaluation Team in SAKIP assessment at the Regional Inspectorate of Solok Regency and to identify the factors that influence it. This study used a qualitative approach with a descriptive method. Research informants were determined through purposive sampling, including the person in charge of the evaluation team, the deputy person in charge/technical controller, the head of the evaluation team, and three members of the evaluation team. Data were collected through interviews, observation, and documentation, then analyzed descriptively. The results of the study show that the work effectiveness of the Evaluation Team is generally moderately effective, although several indicators have not been optimally fulfilled. Indicators of goal achievement, work quality, and timeliness have been implemented well, while indicators of work quantity and job satisfaction have not been fulfilled due to the limited number of evaluators, high workload, the use of a still-manual evaluation system, and the absence of special incentives for the Evaluation Team. Factors influencing work effectiveness include productivity, work motivation, timeliness, and equipment and facilities that remain suboptimal, particularly in the aspect of data processing. The conclusion of the study affirms that the work effectiveness of the Evaluation Team in SAKIP assessment at the Regional Inspectorate of Solok Regency needs to be strengthened through increasing the number of evaluators, developing a digital-based evaluation system, and providing work rewards. The implications of this study provide practical contributions to improving civil apparatus resource management and strengthening the quality of SAKIP evaluation in local government.